In vitro and intracellular inhibitory activities of nosiheptide against Mycobacterium abscessus - Zhu, Rui; Yu, Xia; Zhang, Tingting; Kong, Yaoyao; Wang, Fen; Jia, Junnan; Xue, Yi; Huang, Hairong (Frontiers in Microbiology, 2022)
The high level of inherent drug resistance of M. abscessus makes the infection caused by it very difficult to be treated. The objective of this study was to evaluate the potential of nosiheptide (NOS) as a new drug candidate for treating M. abscessus infections. The microplate AlamarBlue assay was performed to determine the minimum inhibitory concentrations (MICs) of NOS for 28 reference strains of rapidly growing mycobacteria (RGM) and 77 clinical isolates of M. abscessus. Time-kill kinetic and post-antibiotic effect (PAE) of NOS against M. abscessus was evaluated. Its bactericidal activity against M. abscessus in macrophages was determined by intracellular colony numerating assay. NOS manifested good activity against the reference strains of RGM and M. abscessus clinical isolates in vitro. The MICs of NOS against M. abscessus clinical isolates ranged from 0.0078μg/mL to 1μg/mL, and the MIC50 and MIC90 was 0.125μg/mL and 0.25μg/mL, respectively. The pattern of growth and kill by NOS against M. abscessus was moderate with apparent concentration-dependent characteristics, and the PAE value of NOS was found to be 6 h. Furthermore, NOS had low cell toxicity against the THP-1 cell line after 48 hours exposure (IC50=76.7µM). At 4μg/mL, NOS exhibited high intracellular bactericidal activity against M. abscessus reference strains with an inhibitory rate of 62.6% ± 5.04%, comparable to that of clarithromycin at 2 μg/mL. NOS showed suitable inhibitory activities against M. abscessus in vitro and in macrophages and could be a potential drug candidate to treat M. abscessus infection.